Natural products from stem bark of Calophyllum andersonii - Tee, Keng Hong; Ee, Gwendoline Cheng Lian; Wong, Ka Woong; Karunakaran, Thiruventhan; Jong, Vivien Yi Mian; Teh, Soek Sin (Universiti Putra Malaysia Press, 2018)
Phytochemical study on the stem bark of Calophyllum andersonii has resulted in the isolation of five xanthones, namely (1) caloxanthone I, (2) pyranojacareubin, (3) macluraxanthone, (4) caloxanthone C, and (5) euxanthone. In this study, the compounds were subjected to various spectroscopic analyses including FT-IR, GC-MS, 1D and 2D NMR for structural elucidations. Furthermore, these xanthones were obtained for the first time from Calophyllum andersonii, a plant never reported before. All four extracts, namely hexane, chloroform, ethyl acetate and methanol extracts of the plant showed moderate inhibitions against Bacillus subtilis.